Paradox of peroxy defects and positive holes in rocks Part II: Outflow of electric currents from stressed rocks. (15th December 2015) - Scoville, John; Sornette, Jaufray; Freund, Friedemann T.
Highlights: Igneous and high-grade metamorphic r Rocks in the Earth's crust contain peroxy defects, which – upon stressing – release highly mobile positive hole charge carriers. The positive holes can flow out of the stressed rock volume, into and through unstressed rocks, traveling far and fast, at about 100 m/s. Because of their wide spectrum of lifetimes, the number of positive holes activated per unit volume of rock and, hence, the outflow currents, increases steeply with the rate at which stresses are applied, reaching values as high as 10 9 A km −3 when a 20 cm 3 volume of gabbro is stressed within 1–2 ms. The total number of positive holes flowing out is relatively constant and independent of the stress rate, about 10 6 Coulomb km −3 . Abstract: Understanding the electrical properties of rocks is of fundamental interest. We report on currents generated when stresses are applied. Loading the center of gabbro tiles, 30 × 30 × 0.9 cm 3, across a 5 cm diameter piston, leads to positive currents flowing from the center to the unstressed edges. Changing the constant rate of loading over 5 orders of magnitude from 0.2 kPa/s to 20 MPa/s produces positive currents, which start to flow already at low stress levels, <5 MPa. The currents increase as long as stresses increase. At constant load they flow for hours, days, even weeks and months, slowly decreasing with time. When stresses are removed, they rapidly disappear but can be made to reappear upon reloading. These currents are consistent with the stress–activation of peroxy defects, such as O3 Si–OO–SiO3, in the matrix of rock-forming minerals. The peroxy break-up leads to positive holes h, i.e. electronic states associated with O − in a matrix of O 2−, plus electrons, e′. Propagating along the upper edge of the valence band, the h are able to flow from stressed to unstressed rock, traveling fast and far by way of a phonon-assisted electron hopping mechanism using energy levels at the upper edge of the valence band. Impacting the tile center leads to h pulses, 4–6 ms long, flowing outward at ∼100 m/s at a current equivalent to 1–2 × 10 9 A/km 3 . Electrons, trapped in the broken peroxy bonds, are also mobile, but only within the stressed volume.